Response of safflower to foliar spray of nano urea: Response of safflower to foliar spray of nano urea - S A SHINDE; S B GHUGE; P O BHUTADA (Journal of Oilseeds Research, 2023)
The objective of the present study was to investigate the effect of different rates of soil applied nitrogen (100% N, 75% N and 50% N) and foliar spray of nano urea and 2% urea (at flowering and seed filling stages) on growth and yield of safflower. The results showed that the effect of soil applied urea at vegetative stage and foliar applied urea at reproductive stage had significant effect on seed and biological yield (1581, 4249 kg/ha) of safflower and recorded maximum biological yield among given treatments.